Implementasi Blackbox Testing Pada Aplikasi Real-Time Thermal Video Detection (Studi Kasus Deteksi Demam/Covid-19) - Kukuh Yudhistiro; Aditya Galih Sulaksono; Aditya Hidayat Pratama (LPPM STIKI MALANG, 2021)
During the emergence of the Covid-19 pandemic whose vaccines have not been spread evenly, all countries in the world, especially Indonesia have taken several preventive steps to prevent the spread of the virus. One of the initial actions is to detect every person entering and leaving the country through airports or land transportation. This early action was carried out by detecting the body temperature of residents passing in and out of locations such as airports and train stations. The fever detection is generally carried out using a thermal gun in the form of an infrared gun aimed at individuals who pass the inspection. This research discusses a series of tools consisting of a camera with a thermal sensor where the captured data will be processed through software that displays a histogram of the temperature from the chest to the person's head in real time. Each capture result is used as a dataset that can be used for tracing the needs of visitors to public places. In this research, we will discuss functional testing (blackbox) of the application of thermal video detection in case studies of fever detection.